2018
DOI: 10.1007/s00394-018-1770-6
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of vitamin E, γ-oryzanol, and ferulic acid in healthy humans after the ingestion of a rice bran-enriched porridge prepared with water or with milk

Abstract: Rice bran extract-enriched porridge and, to a lesser extent, RBE oil, provide relevant sources of bioaccessible and bioavailable ferulic acid, and could be further developed into functional foods with health potential.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 47 publications
0
1
0
1
Order By: Relevance
“…15 Calvo-Castro et al reported that no intact ferulic acid esters (cycloartenyl ferulate, 24-methylenecycloartanyl ferulate, campesteryl ferulate, and β-sitosteryl ferulate) were detected in the plasma or urine. 63 To our knowledge, the metabolites in the fecal samples after oryzanol intervention have never been studied, we inferred that partly triterpenoids were products of oryzanol. Triterpenoids including 3β-acetoxy-19α-hydroxy-12-ursene, (3β,17α,23 S )-17,23-epoxy-3,29-dihydroxy-27-norlanost-8-en-24-one, 3β-3-hydroxy-18-lupen-21-one, (3β,17α,23 S ,24 S )-17,23-epoxy-3,24,29-trihydroxy-27-norlanost-8-en-15-one, ganoderiol I, barringtogenol C, lucidenic acid N, ganoderic acid K, corosin, trans -3-feruloylcorosolic acid, porrigenin A, isothankunic acid, 2α-hydroxypyracrenic acid, ganoderol A, (1β,2α,3α)-1,2,3,24-tetrahydroxy-12-oleanen-28-oic acid, (3β,17α,23 R )-17,23-epoxy-3,29-dihydroxy-27-norlanost-8-ene-15,24-dione, ganoderic acid α, and ganoderic acid H were significantly regulated by oryzanol in our study.…”
Section: Discussionmentioning
confidence: 88%
“…15 Calvo-Castro et al reported that no intact ferulic acid esters (cycloartenyl ferulate, 24-methylenecycloartanyl ferulate, campesteryl ferulate, and β-sitosteryl ferulate) were detected in the plasma or urine. 63 To our knowledge, the metabolites in the fecal samples after oryzanol intervention have never been studied, we inferred that partly triterpenoids were products of oryzanol. Triterpenoids including 3β-acetoxy-19α-hydroxy-12-ursene, (3β,17α,23 S )-17,23-epoxy-3,29-dihydroxy-27-norlanost-8-en-24-one, 3β-3-hydroxy-18-lupen-21-one, (3β,17α,23 S ,24 S )-17,23-epoxy-3,24,29-trihydroxy-27-norlanost-8-en-15-one, ganoderiol I, barringtogenol C, lucidenic acid N, ganoderic acid K, corosin, trans -3-feruloylcorosolic acid, porrigenin A, isothankunic acid, 2α-hydroxypyracrenic acid, ganoderol A, (1β,2α,3α)-1,2,3,24-tetrahydroxy-12-oleanen-28-oic acid, (3β,17α,23 R )-17,23-epoxy-3,29-dihydroxy-27-norlanost-8-ene-15,24-dione, ganoderic acid α, and ganoderic acid H were significantly regulated by oryzanol in our study.…”
Section: Discussionmentioning
confidence: 88%
“…Para las muestras del grano completo de arroz en granza molido seleccionadas y preparadas, se realizó la extracción de vitamina E por cuadruplicado según lo propuesto por Calvo-Castro et al (2019) e Irías-Mata et al (2017. Por cada réplica se pesaron 200 mg de material molido fresco en un tubo de ensayo, se agregaron 2 mL de una disolución de ácido ascórbico al 1 % en etanol (m/v), 900 µL de agua desionizada y 600 µL de una disolución saturada de hidróxido de potasio.…”
Section: Extracción De Vitamina Eunclassified